Enhancing Digital Accounting Adoption: The Critical Role of Human Resource Competence and Infrastructure Availability - agnia, agnia nurjanah; Fitria Rahmani, Hani (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The reason of this consider is to find out how foundation accessibility and human asset (HR) capabilities influence the selection of computerized bookkeeping. The inquire about utilizes a overview technique with survey information gathering strategies, utilizing expressive and affiliated approaches. Within the Cimahi city locale, 9,087 MSMEs made up the investigate populace. The Slovin approach was utilized within the test choice prepare, yielding 98 respondents as a result. The study's discoveries demonstrate that the application of computerized bookkeeping in MSMEs in Cimahi City is essentially impacted by three variables: the accessibility of offices and framework, the capacity of human assets, and the accessibility of foundation. concurrently includes a favorable and critical affect on the Computerized Bookkeeping Usage. The usage of advanced bookkeeping is affected by human asset capabilities and the accessibility of offices and framework by 75.1%, with the remaining 24.9 ing impacted by components not included within the think about demonstrate (R Square esteem: 0.751).